Multiple Calcium Export Exchangers and Pumps Are a Prominent Feature of Enamel Organ Cells - Robertson, Sarah Y. T.; Wen, Xin; Yin, Kaifeng; Chen, Junjun; Smith, Charles E.; Paine, Michael L. (Frontiers in Physiology, 2017)
Calcium export is a key function for the enamel organ during all stages of amelogenesis. Expression of a number of ATPase calcium transporting, plasma membrane genes (ATP2B1-4/PMCA1-4), solute carrier SLC8A genes (sodium/calcium exchanger or NCX1-3) and SLC24A gene family members (sodium/potassium/calcium exchanger or NCKX1-6) have been investigated in the developing enamel organ in earlier studies. This paper reviews the calcium export pathways that have been described and adds novel insights to the spatiotemporal expression patterns of PMCA1, PMCA4 and NCKX3 during amelogenesis. New data are presented to show the mRNA expression profiles for the four Atp2b1-4 gene family members (PMCA1-4) in secretory-stage and maturation-stage rat enamel organs. These data are compared to expression profiles for all Slc8a and Slc24a gene family members. PMCA1, PMCA4 and NCKX3 immunolocalization data is also presented. Gene expression profiles quantitated by real time PCR show that: 1) PMCA1, 3 and 4, and NCKX3 are most highly expressed during secretory-stage amelogenesis; 2) NCX1 and 3, and NCKX6 are expressed during secretory and maturation stages; 3) NCKX4 is most highly expressed during maturation-stage amelogenesis; and 4) expression levels of PMCA2, NCX2, NCKX1, NCKX2 and NCKX5 are negligible throughout amelogenesis. In the enamel organ PMCA1 localizes to the basolateral membrane of both secretory and maturation ameloblasts; PMCA4 expression is seen in the basolateral membrane of secretory and maturation ameloblasts, and also cells of the stratum intermedium and papillary layer; while NCKX3 expression is limited to Tomes’ processes, and the apical membrane of maturation-stage ameloblasts. These new findings are discussed in the perspective of data already present in the literature, and highlight the multiplicity of calcium export systems in the enamel organ needed to regulate biomineralization.